From desired futures to market realities: examining policy imaginaries and strategies in the globalization of Ayurveda - Kudlu, Chithprabha (Frontiers in Human Dynamics, 2025)
This paper uses the framework of socio-technical imaginaries to examine how Indian state policy envisions the global future of Ayurveda. The paper is structured in two parts. The first part juxtaposes policy narratives with export market data, revealing several ironies arising from a deep misalignment: while science-based innovation is framed as the key path to global legitimacy, the most profitable segments of the global herbal market demand minimal scientific input and lie largely outside this framing. To understand this disconnect, I trace the evolution of dominant imaginaries shaping ISM policy since the colonial period, alongside contesting imaginaries that drive market formation. This analysis shows that a persistent tension between top-down state imaginaries—shaped by the norms of the biomedical global health order—and grassroots market dynamics animated by consumer imaginaries lies at the heart of the observed misalignments. The second part of the paper critically examines the Ayurveda-Biology initiative, which was framed by a broader technoscientific imaginary that positioned Ayurveda not merely as a tradition to be validated, but as a source of conceptual insights to global science. Although the initiative briefly opened space for scientific research sensitive to Ayurvedic epistemology and forged a high-profile network linking scientific institutions, clinicians, and industry actors, it was never institutionally prioritized. Promising findings were met with indifference, exposing the disconnect between rhetorical commitments to innovation and the structural realities of research governance. In practice, regulatory priorities aligned with market demands were given precedence over foundational inquiry and clinical application. At the same time, these governance dynamics reveal the limits of the technoscientific imaginary, which—though dominant in state policy and global governance regimes of traditional medicine—does not fully determine how the field evolves. Ayurveda’s trajectories—both local and global— are also shaped from below, as practitioners, patients, and consumers exercise implicit forms of agency. Their choices—reflected in everyday clinical practice and market demand—continue to influence how Ayurveda evolves along paths that elude formal institutional control, shaped by alternative imaginaries that operate at the margins of, and sometimes beyond, regulatory frameworks.